DIFFERENCES BETWEEN NAHDLATUL ULAMA AND MUHAMMADIYAHIN THE APPLICATION OF THE WILAYATUL HUKMI MATLAK TO THE DETERMINATION OF THE BEGINNING OF THE MONTH OF RAMADAN - Yandi, Akmal (Fakultas Syariah (Syari'ah Faculty ), 2024)
Determining the start of the month of Ramadan is an aspect of differences among large mass organizations in Indonesia, namely Nahdlatul Ulama (NU) and Muhammadiyah, where this determination is very urgent, because it concerns the issue of obligatory worship for every Muslim. This research aims to further explore conflict among the community and find out the methods used by Nahdlatul Ulama (NU) and Muhammadiyah (Majelis Tarjih) in determining the start of the month of Ramadan, especially in the application of matlak and wilayatul hukmi. The method used in this research is library research, while the main objects are journals and library books related to this research. The results of this research are: Nahdlatul Ulama is of the opinion that to determine the beginning of the month, especially those related to worship such as (the beginning of Ramadan, Shawwal, and Zulhijah), the concept of matlak wilayatul hukmi is used, which is the basis of rukyatul hilal bil fi'li, namely seeing the new moon directly in the field. In order to create togetherness in determining and starting the beginning of the month in a government. Meanwhile, Muhammadiyah, through the highest council and the central leadership of Muhammadiyah, determines the start of the month, namely by using the actual reckoning method for the shape of the hilal, namely determining the start of the month if three criteria are met. Firstly, ijtimak (conjunction) has occurred, secondly, ijtimak has occurred before sunset, and thirdly, when the sun sets, the sun is accompanied by the moon above the horizon (a new moon has appeared). And Muhammadiyah uses fundamental thinking in calculating the shape of the new moon that it uses.